Deformation and Resilient Behavior of Hot and Warm Mix Asphalt Concrete - Zainalabidine Nihad Abd Al-Mahdi; Saad Issa Sarsam (Salehan Institute of Higher Education, 2018)
Development of hazardous gases emissions through the production and construction of Hot Mix Asphalt (HMA) have encouraged the transition to Warm Mix Asphalt (WMA) which is considered as one of the best choices of sustainable materials in asphalt pavement. The temperature reduction in the mixing, handling, and compaction of the mix gets in saving energy, cutting emissions and significant cuts in construction costs. In this investigation, two WMA mixtures have been prepared in the laboratory using medium curing cutback (MC-30) and cationic emulsion asphalt. HMA mixture was also prepared for comparison. Marshall size Specimens of (101.6 mm) in diameter and (63.5 mm) in height were constructed from these mixtures and subjected to repeated Indirect Tensile Strength test (ITS) to determine the effect of asphalt type and content on deformation and resilient behavior of asphalt mixture. Another group of cylindrical specimens of (101.6 mm) diameter and (101.6 mm) in height have been constructed from these mixtures and subjected to repeated compressive stresses test to determine the rutting resistance of asphalt mixture. Test results were analyzed and compared. It was concluded that, the permanent deformations for cutback and emulsion treated WMA was higher than that of HMA by (50 and 35) % respectively. The Resilient Modulus (Mr) at 25 ⁰C under repeated (ITS) for cutback and emulsion treated WMA was lower than that of HMA by (39.95 and 27.94) % respectively. On the other hand, the (Mr) for cutback and emulsion treated WMA was higher than that of HMA by (43.75 and 5.47) % respectively under repeated compression load at stress level 0.138 (MPa).